VASILE ALECSANDRI ÎN TINEREȚE - MOȚOC, Făgăraș, Radu (BIBLIOPOLIS, 2020)
The author Radu Moțoc brings to the fore the young years of the classic writer Vasile Alecsandri (1821-1890). V. Alecsandri was a poet, playwright, folklorist, politician, minister, diplomat, founding member of the Romanian Academy, creator of Romanian theater and dramatic literature in Romania, outstanding personality of Moldova and then of Romania throughout the century The 19th century.